2023
DOI: 10.1021/acs.jpcc.3c04686
|View full text |Cite
|
Sign up to set email alerts
|

The Removal Mechanism of U(VI) on nZVI/MoS2 Composites Investigated by Batch, Spectroscopic, and Modeling Techniques

Abstract: A novel nanoscale zero-valent iron/molybdenum disulfide (nZVI/MoS 2 ) composite was synthesized and well characterized in detail. The as-prepared materials were applied for the removal of U(VI) from water solutions under various experimental conditions. The characterizations showed that nZVI/MoS 2 composites exhibited a high surface area and uniform distribution of nZVI. The maximum adsorption capacities of nZVI/MoS 2 obtained from the Langmuir model (71.8 mg/g at pH 4.0 and 25 °C) were higher than that of MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The BET specific surface areas of MoS 2 and nZVI/MoS 2 were 25 and 31 m 2 /g, respectively. The large BET surface area of nZVI/MoS 2 could be ascribed to the incorporation of nZVI nanoparticles, which effectively prevented the aggregation of nZVI and significantly enhanced its dispersion. , Overall, the characterizations showed that nZVI was evenly deposited on the MoS 2 surface, which increased the specific surface area and uniform distribution.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The BET specific surface areas of MoS 2 and nZVI/MoS 2 were 25 and 31 m 2 /g, respectively. The large BET surface area of nZVI/MoS 2 could be ascribed to the incorporation of nZVI nanoparticles, which effectively prevented the aggregation of nZVI and significantly enhanced its dispersion. , Overall, the characterizations showed that nZVI was evenly deposited on the MoS 2 surface, which increased the specific surface area and uniform distribution.…”
Section: Resultsmentioning
confidence: 90%
“…The crystal composition of the nZVI/MoS 2 composite was further confirmed using XRD patterns (Figure C). The diffraction peaks of nZVI at 2θ = ∼58.3, 33.6, and 14.2° were indexed into the (110), (100), and (002) planes of MoS 2 , respectively . The appearance of new diffraction peaks of nZVI/MoS 2 at 2θ = ∼44.8 and 34.2° were attributed to the (110) plane of Fe 0 and the (023) plane of Fe 3 O 4 , respectively .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations